Evaluating the Success of Written Mitigation in Reducing Prison Sentences and Achieving Alternatives to Incarceration for Parole Violations - Nnenna Onyema; Jaime Buseman; Carrie Maldovan (Columbia Social Work Review, 2017)
It is estimated that 2.4 million individuals are incarcerated in federal, state, and county prisons and jails in the United States, the largest number seen in the developed world (Flatow, 2014). In addition, there are an estimated 4.75 million, or 1 in 51, adults under community supervision in the United States (Herberman & Bonczar, 2014). This includes individuals on probation, parole, and other forms of post-prison supervision. There are issues with the mass incarceration system in the United States that extend beyond the sheer number of individuals incarcerated. For instance, people of color make up 30% of the population but 60% of those imprisoned (Kerby, 2012). For the about 850,000 on parole, many face struggles adapting to society and attaining basic needs such as health care, housing, and employment. These factors, among many others, lead these individuals to violate parole and become re-imprisoned, creating a cycle of perpetual contact with the legal system. The Parole Revocation Defense Unit at the Legal Aid Society provides services for those who have had their parole revoked or face parole revocation. Social workers work together with lawyers to provide comprehensive plans to reduce sentences and recommend alternatives to incarceration. One tool, known to be powerful within PRDU at the Legal Aid Society, is written mitigation, a process used to advocate for and provide holistic presentations of clients. This paper evaluates the benefits of written mitigation by looking at the sentencing for 20 cases before and after written mitigation. The findings show that written mitigation was helpful in reducing sentences and resulting in alternatives to incarceration with statistical significance. This information learned contributes to the larger discussion of the relevance of social workers in legal settings to provide holistic services and broader conversations of criminal justice reform and elimination of institutions that produce outcomes that do more harm than good.